Study on Optimization of Blasting Parameters and its Effect on Anchoring Rock Beam of a Underground Workshop - Li, Xin Ping; Zhang, Cheng Liang (Applied Mechanics and Materials, 2011)
The optimum model for blasting parameters of anchoring rock beam is established and its blasting parameters are optimized by making use of a strong mapped function of the neural networks technology with the typical samples of other practical smooth blasting parameters. The explosive types, the extent of joint development of rock mass, the diameter of bore-hole, the depth of bore-hole, the linear charge density, the burden line of least resistance and the spacing of bore-hole are considered as the primary effective factors in the excavation of anchoring rock beam. In the meantime, the experimental blasting parameters for anchoring rock beam are determined by the in-site blasting experiments of the protective layer and platform of rock mass in similar conditions. The results show that the in-site experimental blasting parameters are preferably identical to those of the optimum design. The acoustic wave examination for the blasting of the protective layer and platform of rock mass indicates that the blasting effect is satisfied and its smaller loose ring of surrounding rock mass is obtained.